The Role of Competitor Analysis, Market Orientation, and Service Quality in Working Capital Management and Operational Leverage as Links to Financial Stability of Manufacturing Companies Listed on the IDX: A Qualitative Approach - Abubakar, Herminawaty; Ruslan, Muhlis; Suriani, Seri (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study investigates the interconnectedness of competitor analysis, market orientation, service quality, working capital management, and operational leverage in shaping organizational financial stability. The research aims to identify strategic implications for effective management of these factors and provide insights for both theoretical understanding and managerial practice. The study employs a systematic literature review methodology to analyze existing research across various domains and synthesizes findings to elucidate the relationships among the variables. The results reveal that competitor analysis serves as a foundational element in strategic planning by providing insights into market dynamics and competitive positioning. Market orientation complements this by emphasizing customer-centricity and responsiveness to market needs, while service quality emerges as a critical determinant of organizational success. Effective working capital management and operational leverage strategies significantly impact financial stability by optimizing resource utilization and cost efficiency. The findings suggest that organizations must adopt a multidimensional approach to strategic management, integrating insights from marketing, finance, and operations. Managerial implications include prioritizing investments in market intelligence, fostering a customer-centric culture, optimizing working capital management practices, and carefully managing operational leverage. Collaboration across functional areas and agile decision-making are essential for adapting strategies to dynamic market conditions. Overall, the study contributes to a deeper understanding of the complex interplay among these factors and provides actionable recommendations for enhancing financial stability and sustaining competitive advantage.